METHODS OF ACHIEVING EFFICIENCY THROUGH PSYCHOLOGICAL COACHING IN IMPROVING STUDENTS' COMMUNICATION - Sanjar SHOTEMIROV (Scholar Express Journal, 2023)
This article covers the topic of psychological importance of formation of speaking and communication skills in students. The article also provides information on the important role of communication as a social and psychological reality
Keywords: Social-psychological training; mental processes; human personality; position